1999
DOI: 10.2960/j.v25.a17
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Rate of Sexual Maturity and the Effect on Spawning Stock for Georges Bank and Gulf of Maine Atlantic Cod Gadus morhua Stocks

Abstract: Stocks of Atlantic cod, Gadus morhua, off the coast of New England have been heavily exploited by distant water fleets in the 1960s and 1970s and by domestic fisheries in recent years and abundance has declined. Maturation data collected by Northeast Fisheries Science Center research bottom trawl surveys from 1970-98 were examined to determine if the rate of sexual maturation of Atlantic cod varied in response to fluctuations in stock density, growth, or ambient temperature. Median age and length at maturity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 23 publications
0
42
0
Order By: Relevance
“…Often in fisheries stock assessments these variables are assumed to be constant over extensive spatial and temporal scales (Rijinsdorp et al 1991, Marshall et al 1999, with little regard for the plasticity ) and potential fecundity of a standard fish, 70, 90 and 120 cm length cod from different areas in the North Atlantic, the Baltic and the North Sea in these flexible life history characteristics to fishing exploitation and environmental perturbations (Stearns & Crandall 1984). Indeed, similar to other cod stocks throughout the north Atlantic (Holdway & Beamish 1985, Godø & Moksness 1987, Trippel et al 1997b, Begg et al 1999, Cardinale & Modin 1999, O'Brien 1999, the Icelandic cod stock demonstrated significant sexual, spatial and temporal variation in age and size at maturity (Fig. 2) that were strongly affected by growth and condition (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Often in fisheries stock assessments these variables are assumed to be constant over extensive spatial and temporal scales (Rijinsdorp et al 1991, Marshall et al 1999, with little regard for the plasticity ) and potential fecundity of a standard fish, 70, 90 and 120 cm length cod from different areas in the North Atlantic, the Baltic and the North Sea in these flexible life history characteristics to fishing exploitation and environmental perturbations (Stearns & Crandall 1984). Indeed, similar to other cod stocks throughout the north Atlantic (Holdway & Beamish 1985, Godø & Moksness 1987, Trippel et al 1997b, Begg et al 1999, Cardinale & Modin 1999, O'Brien 1999, the Icelandic cod stock demonstrated significant sexual, spatial and temporal variation in age and size at maturity (Fig. 2) that were strongly affected by growth and condition (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In fisheries science, maturation is usually described by two indices: the age at which 50% of individuals are mature (A 50 ), and the length at which 50% of individuals are mature (L 50 ) (Jørgensen 1990, Chen and Paloheimo 1994, Morgan and Colbourne 1999, O'Brien 1999. In many fish stocks these indices suggest that maturation schedules have changed during the last 30 years: fish reproduce younger and younger, and at smaller and smaller sizes (Jørgensen 1990, Rijnsdorp 1993a, b, Morgan et al 1999, O'Brien 1999.…”
Section: Introductionmentioning
confidence: 99%
“…In many fish stocks these indices suggest that maturation schedules have changed during the last 30 years: fish reproduce younger and younger, and at smaller and smaller sizes (Jørgensen 1990, Rijnsdorp 1993a, b, Morgan et al 1999, O'Brien 1999. These shifts in maturation could be due to purely phenotypic changes resulting from long-term trends in temperature, population density, or any other relevant aspect of the ambient environment.…”
Section: Introductionmentioning
confidence: 99%
“…These declines have often coincided with marked changes in the ages and sizes at which fish commence reproducing (e.g. Haug & Tjemsland 1986, Jørgensen 1990, Rijnsdorp 1993, Trippel 1995, O'Brien 1999, Bromley 2000. In most cases, the fish now mature at earlier ages and smaller sizes than they did some decades ago.…”
Section: Introductionmentioning
confidence: 99%